Water Vending in Nigeria - A Case Study of Festac Town, Lagos, Nigeria - Olajuyigbe, A. E; Rotowa, O.O; Adewumi, I.J (Richtmann Publishing, 2012)
In most developing countries, it has been recognized that conventional water utilities have fallen short in providingadequate water services to populations. Festac Town, Lagos, Nigeria is a typical community that is presently not being servicedby such water utilities due to the inability of the Water Supply Agency (WSA) in supplying water to the area. Householdstherefore seek other alternative sources including water vending. This paper examined the role of water vending in householdwater supply delivery in this community. It identified the sources of water supply by the vendors, assessed their level ofpatronage among households and identified the problems associated with their operations. For the study, a total number of1,139 and 57 households and vendors were selected by simple random sampling respectively. The result showed that there aretwo main categories of water vending namely; formal and informal vendors. All formal vendors obtain their supplies fromimproved sources while most informal vendors obtain theirs from unimproved sources. Majority of the households considervended water as a coping strategy since they are aware of the safety implications. Therefore, most households are willing to payfor water services. The paper canvassed the need for government to recognize the role of water vending in water delivery. Itadvocated for a secondary level of supply mechanism among vendors in a bid to ensure quality water supply. The paperconcluded that the most sustainable strategy would be to resuscitate the moribund piped water supply system earlier initiated bythe WSA.